Fruits of victory : the Woman's Land Army of America in the Great War - Weiss, Elaine, 1952- (Washington, D.C. : Potomac Books, 2008)
The women who kept the farms going while the soldiers were Over There.
Liberty Day -- The girl with a hoe behind the man with a gun. The right to serve : a British Land Army ; Female preparedness ; An agricultural army ; Suffrage agriculture ; Soil sisters ; A feminine invasion of the land : the Bedford Camp ; Farmerettes abd Hoover Helpers : Fall 1917 ; Women on the land ; A hysterical appeal ; A fine propaganda : the Fair Farmerette and her publicity machine ; Enlist now! -- The Patriot Farmerette. In bifurcated garb of toil : California ; Hortense Powdermaker in Maryland ; Cultivating the soothing weed : Connecticut ; Libertyville : Illinois ; Girls who thought potatoes grew on trees : New England ; The Farmerette in Wanamaker's window : selling the Land Army in New Jersey ; Georgia cotton ; Harsh terrain ; Miss Diehl and the Wellesley Experiment Station ; Tiller, planter, gleaner : New York ; Marriage of convenience ; A hungry world ;Carry on ; Farmerette redux : 1919 and beyond.
Includes bibliographical references (pages 301-306) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Women's Land Army of America -- History; Women's Land Army of America; World War, 1914-1918 -- Women -- United States; World War, 1914-1918 -- War work -- United States; World War, 1914-1918 -- Participation, Female; World War, 1914-1918 -- Food supply -- United States; World War, 1914-1918 -- Economic aspects -- United States; Women farmers -- United States -- History -- 20th century; Guerre mondiale, 1914-1918 -- Femmes -- États-Unis.; Guerre mondiale, 1914-1918 -- Participation des civils -- États-Unis.; Guerre mondiale, 1914-1918 -- Participation des femmes; Guerre mondiale, 1914-1918 -- Alimentation -- États-Unis.; Guerre mondiale, 1914-1918 -- Aspect économique -- États-Unis.; Agricultrices -- États-Unis -- Histoire -- 20e siècle.; HISTORY -- Military -- World War I; Economics; Food supply; Military participation -- Female; War work; Women; Women farmers; United States; Weltkrieg; Heimatfront; Landwirtschaftlicher Betrieb; Landarbeiterin; USA; 1900-1999; History